THE ROLE OF WIVES AS BREADWINNERS AND ITS IMPACT ON THE INTEGRITY OF THE HOUSEHOLD FROM AN ISLAMIC PERSPECTIVE - Muhammad Shidqi Pribadi; Teguh Dwi Cahyadi (Universitas Nurul Jadid, 2025)
One of a husband’s primary responsibilities is to provide financial support for his family. Yet not all husbands are able to fulfill this duty adequately, leading to weakened household economies and compelling wives to contribute as breadwinners. This phenomenon is evident among the families of workers at the synthetic hair factory in Purbalingga Regency, where many wives assume the role of principal income earner to meet their household needs. This study aims to identify the factors that drive wives to become the main breadwinners, particularly within the families of factory employees in Purbalingga, examine the effects of this role on marital cohesion, and explore the Islamic perspective on wives as primary providers. Employing a qualitative case-study approach, the research reveals three key findings: (1) economic necessity, stemming from insufficient spousal income, and instances of husbands being unable to work due to illness or by mutual agreement compel wives to take on earning responsibilities; (2) while wives’ income-generating role can enhance family welfare stability, it may also reduce family quality time, create a double burden of domestic and economic duties, hinder communication effectiveness, and heighten role-imbalance conflicts; and (3) within Islamic jurisprudence, wives are permitted to seek livelihood support when their husbands’ earnings fall short, provided they observe Shariah-compliant conditions and limitations; however, any contravention of these religious guidelines renders such work impermissible.